2016
DOI: 10.1016/j.jpsychires.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

The association between post-traumatic stress disorder and lifetime DSM-5 psychiatric disorders among veterans: Data from the National Epidemiologic Survey on Alcohol and Related Conditions-III (NESARC-III)

Abstract: This study examined the prevalence, correlates and psychiatric comorbidity of Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) posttraumatic stress disorder (PTSD) in a nationally representative sample of U.S. veterans using data from the National Epidemiologic Survey on Alcohol and Related Conditions-III (n=3119 veteran respondents). The overall prevalence of lifetime PTSD was 6.9%. Lifetime PTSD prevalence was higher among veterans who were female (13.2%), aged 18–29 years (15.3%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
101
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(108 citation statements)
references
References 46 publications
(59 reference statements)
5
101
0
2
Order By: Relevance
“…Respondents further had to report symptom duration of ≥1 month and clinically significant impairment or distress. The requirement of ≥3 D and E symptoms is higher than the 2 symptoms from each cluster required for DSM-5 criteria [17], but has been used in other studies based on NESARC-III data [8, 15, 41]. Test–retest reliability of past-year PTSD was fair (0.41) and reliability of the dimensional PTSD criteria scale was good [intraclass correlation coefficient (ICC) = 0.69] [42].…”
Section: Methodsmentioning
confidence: 99%
“…Respondents further had to report symptom duration of ≥1 month and clinically significant impairment or distress. The requirement of ≥3 D and E symptoms is higher than the 2 symptoms from each cluster required for DSM-5 criteria [17], but has been used in other studies based on NESARC-III data [8, 15, 41]. Test–retest reliability of past-year PTSD was fair (0.41) and reliability of the dimensional PTSD criteria scale was good [intraclass correlation coefficient (ICC) = 0.69] [42].…”
Section: Methodsmentioning
confidence: 99%
“…This study reported a 33.2% prevalence of alcohol use disorders in community veterans without posttraumatic stress disorder (PTSD), and a rate of 54.5% in those with PTSD. Similarly, the investigators reported an 8.3% prevalence of drug use disorder in veterans without PTSD, which rises to 27.2% in veterans with PTSD . In a recent analysis of the NESARC data, a comparison between veteran and community samples revealed veteran rates were roughly similar to those of the community sample for street drugs and prescription use, but they were far higher for alcohol and tobacco use.…”
Section: Purposementioning
confidence: 91%
“…A recent review of the epidemiology of SUDs in US veterans found widely varying estimates based on type of data (administrative vs direct diagnostic assessment) and whether or not the sample targeted both treated and untreated SUD . There are a range of community‐based studies of both treated and untreated SUD that determine veteran status based on self‐report . These studies can help inform VHA about veteran SUD and treatment in the community and complement prevalence and treatment estimates based on VHA administrative data.…”
Section: Purposementioning
confidence: 99%
See 2 more Smart Citations